Reporting Time Horizons in Randomized Controlled Trials in Plastic Surgery: A Systematic Review. Issue 6 (December 2018) - Mowakket, Sadek; Karpinski, Marta; Gallo, Lucas; Gallo, Matteo; Banfield, Laura; Murphy, Jessica; Waltho, Daniel; Copeland, Andrea; Moltaji, Syena; Thoma, Achilleas
Abstract : Background: Current guidelines for randomized controlled trial reporting do not require authors to justify their choice of time horizon. This is concerning, as the time horizon when an outcome is assessed has important implications for the interpretation of study results, and resources allocated to an investigation. Therefore, this study seeks to examine the standards of time horizon reporting in the plastic surgery literature. Methods: This is a systematic review of plastic surgery randomized controlled trials published within the past 4 years. The MEDLINE database was searched to yield relevant studies. All studies included were English language, prospective, nonpharmaceutical randomized controlled trials, comparing two plastic surgical interventions. Studies were classified into plastic surgery domains, and information regarding study population, time horizon reporting, and justification of chosen time horizon, was extracted. Results: The search retrieved 720 articles, of which 103 were eligible for inclusion. Time horizons were reported as either a standardized time point at which all patients were assessed, or a follow-up duration range, or were not reported at all. Although most studies (85.4 percent) reported a standardized time horizon, the majority (85.4 percent) failed to provide a valid justification to support their selection of time horizon. Conclusions: Clinical investigators failed to justify their choice of time horizon in the majority of published randomized controlled trials. To limit heterogeneity, time horizons for given interventions should be standardized to improve validity of outcome assessments, enable future pooling of results, and increase research efficiency. Abstract : Supplemental Digital Content is available in the text.